2016
DOI: 10.1111/ppe.12267
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Algorithm to Determine Spontaneous versus Provider‐Initiated Preterm Birth in US Vital Records

Abstract: The algorithm distinguished spontaneous from indicated preterm birth, using birth certificates, with good accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…We approached the categorisation of this variable from a clinically minded standpoint and thus did not include stillbirths or those born below the limit of viability. Using a validated algorithm developed for use with US vital records, we stratified preterm births by type, categorising them as spontaneous (preceded by spontaneous membrane rupture and/or uterine contractions) or clinician‐initiated (labour or delivery occurred secondary to medical intervention) . The kappa statistic for the algorithm is 0.83 (0.70, 0.95), indicating excellent agreement between algorithm‐assigned and manually assigned preterm birth type…”
Section: Methodsmentioning
confidence: 99%
“…We approached the categorisation of this variable from a clinically minded standpoint and thus did not include stillbirths or those born below the limit of viability. Using a validated algorithm developed for use with US vital records, we stratified preterm births by type, categorising them as spontaneous (preceded by spontaneous membrane rupture and/or uterine contractions) or clinician‐initiated (labour or delivery occurred secondary to medical intervention) . The kappa statistic for the algorithm is 0.83 (0.70, 0.95), indicating excellent agreement between algorithm‐assigned and manually assigned preterm birth type…”
Section: Methodsmentioning
confidence: 99%
“…We used a previously described algorithm that has undergone validation by comparison of birth certificate categorization to medical chart data. 12,13 Limitations of our findings should be considered. First, this study is a retrospective one, based on data reported in natality records, and is subject to errors inherent to vital statistics such as errors in self-reporting and misclassification.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…PTB was defined as delivery < 37 weeks of gestation. PTB subtype was classified as spontaneous (S-PTB) or indicated (I-PTB) using available birth certificate data according to a previously documented and validated algorithm by Klebanoff et al 12,13 Briefly, S-PTB was defined as PTB after spontaneous labor or preterm rupture of membranes. I-PTB was defined as a preterm delivery for a maternal or fetal indication that required provider initiation of delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Birth certificate‐based algorithms have been developed for research on other outcomes (e.g., spontaneous vs. provider‐initiated preterm birth) (Klebanoff et al. ) and claims data‐based algorithms exist for elective cesarean (Gregory et al. ), and here, we applied a similar approach to categorize term cesarean deliveries.…”
Section: Methodsmentioning
confidence: 99%
“…We developed an algorithm to define four categories of cesarean delivery based on the presence of baseline indications for cesarean, the presence of a trial of labor, and the presence of other markers of labor as recorded on the birth certificate ( Figure 1). Birth certificate-based algorithms have been developed for research on other outcomes (e.g., spontaneous vs. provider-initiated preterm birth) (Klebanoff et al 2016) and claims data-based algorithms exist for elective cesarean (Gregory et al 2002), and here, we applied a similar approach to categorize term cesarean deliveries.…”
Section: Categorizing Cesarean Deliverymentioning
confidence: 99%